China’s carbon labeling legal system and green supply chain management from the perspective of sustainability: status quo, implementation problems and legislative recommendations - Jiangang Qi; Zhaodi Yu (Carbon Management)
China’s carbon labeling system (CLS) is a key environmental policy tool that drives the green transformation of supply chains, improves supply chain efficiency and competitiveness, reduces corporate costs, and enhances risk management capabilities. The aim of this study is to investigate the positioning of the CLS within the environmental policy-legal framework and identify its implementation challenges from a legal perspective. Employing a normative analysis method, the study comprehensively examines administrative regulatory documents, standardization documents, and industry self-regulation norms issued since 2010 by central and local governments, as well as industry self-regulatory associations. The findings reveal that the CLS remains a policy tool rather than a legislative tool, with no formal legislative regulation currently in place. To address this gap, the study proposes a comprehensive framework to establish a legal foundation for the CLS by defining its legal principles, clarifying its attributes, and constructing specific legal and oversight systems. This transformation would formalize the CLS as a legislative tool, thereby promoting green supply chain transformation and optimizing decision-making. These findings provide valuable insights for scholars, policymakers, and legislators, offering a practical roadmap for advancing CLS legislation and supporting China’s dual carbon targets.